ChemInform Abstract: Visible‐Light‐Mediated Generation of Nitrogen‐Centered Radicals: Metal‐Free Hydroimination and Iminohydroxylation Cyclization Reactions. Issue 12 (March 2016) - Davies, Jacob; Booth, Samuel G.; Essafi, Stephanie; Dryfe, Robert A. W.; Leonori, Daniele
Abstract: The novel hydroimination and iminohydroxylation cyclization reactions proceed via formation of iminyl radicals from O‐aryl oximes.